Interobserver agreement and validity of bedside 'positive signs' for functional weakness, sensory and gait disorders in conversion disorder: a pilot study. Issue 4 (3rd July 2014) - Daum, Corinna; Gheorghita, Fulvia; Spatola, Marianna; Stojanova, Vesna; Medlin, Friedrich; Vingerhoets, François; Berney, Alexandre; Gholam-Rezaee, Mehdi; Maccaferri, Giorgio E; Hubschmid, Monica; Aybek, Selma
Abstract : Background: Conversion disorder (CD) is no longer a diagnosis of exclusion. The new DSM-V criteria highlight the importance of 'positive signs' on neurological examination. Only few signs have been validated, and little is known about their reliability. Objective: The aim was to examine the clinical value of bedside positive signs in the diagnosis of CD presenting with weakness, gait or sensory symptoms by assessing their specificity, sensitivity and their inter-rater reliability. Patients and methods: Standardised video recorded neurological examinations were performed in 20 consecutive patients with CD and 20 'organic' controls. Ten previously validated sensory and motor signs were grouped in a scale. Thirteen additional motor/sensory 'positive signs', 14 gait patterns and 1 general sign were assessed in a pilot validation study. In addition, two blinded independent neurologists rated the video recordings to assess the inter-rater reliability (Cohen's κ) of each sign. Results: A score of ≥4/14 on the sensory motor scale showed a 100% specificity (CI 85 to 100) and a 95% sensitivity (CI 85 to 100). Among the additional tested signs, 10 were significantly more frequent in CD than controls. The interobserver agreement was acceptable for 23/38 signs (2 excellent, 10 good, 11 moderate). Conclusions: Our study confirms that six bedside 'positive signs' are highly specific for CD with good-excellent inter-rater reliability; we propose to consider them as 'highly reliable signs'. In addition 13 signs could be considered as 'reliable signs' and six further signs as 'suggestive signs' while all others should be used with caution until further validation is available.